ChemInform Abstract: Equilibration of the [2 + 2] Cycloaddition of Silyl Enol Ethers Catalyzed by Ethylaluminium Dichloride: Diastereoselectivity Switch in the Synthesis of Fused Cyclobutanes. Issue 51 (23rd December 2014) - Hata, Kenji; Arichi, Norihito; Yamaoka, Yousuke; Yamada, Ken‐ichi; Takemoto, Yoshiji; Takasu, Kiyosei
Abstract The reaction of silyl enol ethers with acrylate (II) gives the corresponding [2 + 2] cycloadducts.